Study of Biofilm Formation by Phosphate Solubilising Bacteria on Rare Earth Elements Phosphate Minerals - Van Alin, Arya (Curtin University, 2024)
Klebsiella aerogenes, a phosphate-solubilising microorganism, formed biofilm on monazite in three stages: initial attachment, mature biofilm, and dispersion. The eDNA produced aids in initial attachment and mechanical stability. Biofilm was formed on and around physical imperfections, leading to mineral surface erosion. Secondary ion mass spectrometry analysis showed evidence of complex formation between monazite’s rare earth content and organic acid residues produced by the bacteria.